Prognostic Factors for Cancer-Specific Survival and Disease-Free Interval of Dogs with Mammary Carcinomas - Elaine da Silva Soares; Fabrício Luciani Valente; Carolina Camargos Rocha; Carlos Eduardo Real Pereira; Thaís Barroso Sarandy; Fabiano Luiz Dulce de Oliveira; Sabrina Loise de Morais Calado; Andréa Pacheco Batista Borges (Veterinary Medicine International)
Canine mammary tumors (CMTs) are the most diagnosed neoplasms in dogs; however, there are few studies analyzing the influence of epidemiological, clinicopathological, and histopathological data on cancer-specific survival (CSS), disease-free interval (DFI), and overall survival (OS) in a large cohort. To contribute to the understanding of the biological behavior of this neoplasm, 385 cases were analyzed, 89% malignant, 4% benign, and 7% non-neoplastic lesions. Among the dogs diagnosed with malignant neoplasms, 86% had early clinical stages (I–III), while 14% had regional or distant metastasis at the time of diagnosis. Carcinoma in a mixed tumor was the most frequent histological type with 44% of the cases and had the best prognosis. Analyzed factors such as the presence of pseudocyesis, previous history of the disease, advanced clinical stage (IV-V), and presence of ulceration obtained significant results for CSS, DFI, and OS through univariate analysis and had a negative impact on the survival of the patients. Multivariate analysis showed that histological grading and age proved to be the best independent parameters for the prognostic evaluation of CSS and DFI in this study. These factors were also significant in the overall survival analysis. Therefore, these parameters should be considered valuable risk and prognostic factors for CMTs.